PUBLIC PRACTICE OF USING BURIAL PLACES IN THE HETMAN STATE THE SECOND HALF OF THE XVIII CENTURY (City: History, Culture, Society, 2021)
The article deals with studying the burial places in Hetman State of the second half of XVIIIth century. There were a few alternates of burial places for dead in Hetman State, except churchyards (hermit’s caves, homestead burials, skudelnitsya, crossroads, kladbishchenskie mesta).The function of the area around the church wasn’t limited by the burial place for deads. Churchyard was under the local priest control. However, this circumstance did not contribute to the proper care of this area. Churchyards were overflowing with manure and attracted grave robbers.We made an emphasis on the difference between the terms “cemetery” and “churchyard”. The churchyard significance in the space of early modern town was special. The deads had an additional guarantee of salvation at the Last Judgment, resting in the consecrated land.In the article particular attention is focused on the Russian imperial government attempt to organize burial places outside the settlements of the Hetman State. It was caused by trying to organize the functioning of a “well-regulated state” аfollow the West European model. In this regard, the relevant imperial legal framework was created. It regulated the arrangement of specially designated places for burial of the dead (“kladbishchenskie mesta”).It was found out that the imperial government activities of cemeteries arrangement and numerous ecclesiastical demands to arrange the burial grounds were not a unique phenomenon for Europe at that time. Churchyards lost their functions as sites for mass festivities, market places, shelters for needy or simply closed during the XVIIIth century. They were replaced by modern cemeteries, which people visit exclusively to perform mourning rituals.It was found that the imperial authorities weren’t successful in cemeteries organizing. The faile was caused by priests who had to arrange cemeteries. However, they could not arrange burial places on their own. The parishioners didn’t help, although most of the dead found their last rest in the cemeteries. We need to add that some wealthy believers could simply resort to the practice of homestead burial and build a family crypt. As to the poorest parishioners, suicides, beggars, executed criminals, vagrants they fell into the skudelnitsya.Thus, there were alternative burial places for the dead, and Hetman State cemeteries were a multifunctional area. Imperial reform aimed to arrange the dead burial places according to European trends but progressed slowly. Its implementation, even in towns, lasted for almost 100 years.
Keywords: town; churchyard; cemetery; homestead burial; skudelnytsia; Hetman State